Cortisol–CRP synchrony and mood recovery under clustered psychosocial stress in emerging adults - Fatin Nabila Abd Latiff; Dawn A. Stoner; Kah Lun Wang; Kok Bin Wong (PLoS ONE, 2026)
Psychosocial stress involving multiple life changes has well-documented effects on health, yet the physiological mechanisms linking stress exposure to emotional recovery remain incompletely understood. This simulation study examines how clustered life stress, quantified through the Holmes and Rahe Social Readjustment Rating Scale (SRRS) and Life Change Units (LCUs), influences synchrony between cortisol and C-reactive protein (CRP), and how this coupling predicts mood recovery in emerging adults. Using fully synthetic longitudinal data parameterized from published empirical ranges and established biometric patterns, we modeled cortisol–CRP coordination across varying LCU loads and buffering capacities. Results indicated that higher cumulative LCUs, particularly when stressors were temporally clustered, were associated with disrupted cortisol–CRP synchrony and delayed mood rebound. Conversely, stronger physiological coupling between endocrine and immune responses predicted more rapid emotional recovery, suggesting a potential biomarker of stress resilience. These findings identify a bi-axial pathway through which life stress may influence psychological outcomes and underscore the importance of multisystem coordination during vulnerable developmental periods. By integrating a validated stress inventory with biologically grounded simulation, this study contributes novel insights into stress responsivity and affective adaptation.